Pengaruh Seks Edukasi terhadap Kekerasan Seksual pada Anak Usia Dini: Literature Review - Bella, Frisca Nelya; Riya, Rosa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Sexual violence is a serious threat that often makes children victims, especially young children. Children are included in a vulnerable group, so children must receive special protection for their physical and mental needs. One of them is protection from the threat of sexual violence. Based on the data obtained, the number of incidents of sexual violence against children in Indonesia continues to increase, even though various efforts have been made by the government. One effort that can be made by parents and educators is by providing sex education. The aim of the research is to analyze and examine journals related to the influence of sex education on sexual violence in early childhood. This research is a quantitative research with a literature review method using the Google Scholar and PubMed databases, study year 2018-2022 using JBI critical appraisal with a Quasi- experimental study based on PRISMA and the number of articles accepted was (n=8). The results of the research show that various sexual education methods such as modified engklek games, picture stories, audio visuals, picture books, songs, snakes and ladders media, busy books, and role play methods can influence and increase children's knowledge of preventing sexual violence.